Efeito do treinamento físico moderado sobre a injúria renal aguda induzida pela gentamicina - Juliana Barros Almeida (2014)
Although beneficial effects of exercise training on cardiovascular system are well stablished, data regarding exercise effects on other physiological systems as renal system are scarce. Thus, the aim of this study was to investigate the effect of moderate aerobic exercise training in improving acute renal injury induced by gentamicin (GM). Experiment with Wistar rats lasted for 5 weeks. In the 1st week rats were adapted to treadmill and metabolic cages where they were kept individually. Rats were divided into sedentary (Sed) and trained (T) groups. Sed and T groups were then divided into Sed saline (Sed SAL), Sed GM, T saline (T SAL) and T GM subgroups. Exercise training of T groups (T SAL and T GM) in treadmill (18 meters/min, 30 min/day, 3 days/week, 4 weeks) started in the 2nd week and lasted until 5th week. Rats of Sed groups (Sed SAL and Sed GM) also had access to treadmill (5 meters/min, 5 min/day, 3 days/week, 4 weeks). In 2nd week GM (80 mg/kg/day, 0.1 ml/100g) was administered to rats of Sed GM and T GM groups, subcutaneously (s.c.), for 5 days. Rats of Sed SAL and T SAL groups were injected with 0.9% NaCl (sc), for 5 days. Urine and blood were collected at the end of each week in order to evaluate renal function parameters. At the end of experiment, kidneys were collected for histological and morphometric analysis. Data were analysed by One-way Anova followed by Newmann-Keuls test or by paired t test. An improvement in renal function of T GM group was observed in 2nd and 3rd weeks of training. In 2nd week some renal parameters were as following: plasma creatinine (T GM, 0.54 ± 0.09 vs Sed GM, 1.08 ± 0.15 mg/dl), creatinine clearance (T GM, 1.36 ± 0.22 vs Sed GM, 0.57 ± 0.22 L/24h), FEH2O (T GM, 1.51 ± 0.38 vs Sed GM, 7.46 ± 01.89%), FENa+ (T GM, 0.86 ± 0.15 vs Sed GM, 2.60 ± 1.00%). In addition, proteinuria in the 3rd week was: T GM, 9.45 ± 1.51 vs Sed GM, 17.77 ± 3.95 mg/24h and, at the end of experiment, morphometric analysis showed: T GM group, 54.23 ± 7.30 vs Sed GM, 92.15 ± 18.48 cells/field and intersticial area in m2: T GM, 7,934.8 ± 1,095.5 vs Sed GM, 10,711.0 ± 1097.7). Renal changes usually started in 2nd week and remained in 3rd week reaching basal levels after that for most renal parameters evaluated. Data suggest that moderate aerobic training induces an improvement in renal damages observed in acute renal injury induced by GM.